Roof renovation process / Nur Aliah Abd Hadi - Abd Hadi, Nur Aliah (Universiti Teknologi MARA UiTM,Perak, 2022)
The roof is one of the most important structural elements of a building. A roof plays several functions in the performance of a house and these functions in the performance of a house and the function need to be fully understood to create a suitable and comfortable building as well as privacy and protection from the weather. This report will explain about the process of renovation works on roof element. This report was conducted for the dismantle and installation a new concrete tile of the roof of a double storey Air Force quarters house in Pangkalan INSMAT, TUDM Kinrara, Daerah Petaling, Selangor Darul Ehsan. This objective of this report is to identify the process of roof renovation concrete tiles at the quarter’s bungalow. This report will also look the advantages and disadvantages of concrete tiles and will determine the roofing problems and solutions.